2007
DOI: 10.1021/ja074956m
|View full text |Cite
|
Sign up to set email alerts
|

Boron Rings Enclosing Planar Hypercoordinate Group 14 Elements

Abstract: Sets of boron rings enclosing planar hypercoordinate group 14 elements (ABn(n-8); A = group 14 element; n = 6-10) are designed systematically based on geometrical and electronic fit principles: the size of a boron ring must accommodate the central atom comfortably. The electronic structures of the planar minima with hypercoordinate group 14 elements are doubly aromatic with six pi and six in-plane radial MO systems (radial MOs are comprised of boron p orbitals pointing toward the ring center). This is confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
121
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 88 publications
(114 reference statements)
5
121
0
4
Order By: Relevance
“…To the best of our knowledge, the only known aromatic representative for this class is the tropylium cation (C 7 H 7 + ) and a recently proposed boron wheel isomer of CB 7 À . [12] Herein, using quantum chemical calculations, we show that the Cu 7 Sc bimetallic cluster is another planar aromatic system having D 7h point group symmetry.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, the only known aromatic representative for this class is the tropylium cation (C 7 H 7 + ) and a recently proposed boron wheel isomer of CB 7 À . [12] Herein, using quantum chemical calculations, we show that the Cu 7 Sc bimetallic cluster is another planar aromatic system having D 7h point group symmetry.…”
Section: Introductionmentioning
confidence: 93%
“…[25] Note that CMO-NICS(1) zz has been applied recently to measure the aromaticity of the D 8h symmetry SiB 8 boron wheel. [12] Figures 3 and 4 show the total NICS(1) zz and NICS(2) zz decompositions, respectively. Also shown are the sums of their canonical molecular decompositions to valence orbitals having no or one nodal plane in the ring plane, denoted by valence sigma and valence pi, repectively.…”
Section: Wwwchemphyschemorgmentioning
confidence: 99%
“…[14] On the other hand, extensive experimental and theoretical studies on carbon-boron mixed clusters have been carried out [15][16][17] since a prediction on the existence of planar hexa-coordinated carbon in B 6 C 2À clusters. [15] Boron-silicon compounds have attracted considerable interest due to their potentially important applications in the fields of semiconductor materials and thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] A series of planar wheel-type boron rings with a main group atom in the center and coordination numbers 6-10 have been probed theoretically. [12][13][14] So far the joint PES and ab initio studies of aluminum-doped boron clusters showed that the aluminum atom avoids the central position in the AlB 6 À , AlB 7 À , AlB 8 À , AlB 9 À , AlB 10 À , and AlB 11 À systems.[ [15][16][17] Recently, a transition-metal-doped boron cluster, RuB 9 À , with the highest coordination number known to date was reported.[18] We developed a chemical bonding model, which allows the design of planar molecules with high coordination numbers.[18] According to the model, 2n electrons in the MB n species form n 2c-2e peripheral B-B s bonds. The remaining valence electrons form two types of delocalized bonding, in-plane s and out-of-plane p bonding, and therefore, should satisfy the (4N + 2) Hückel rule separately for s and p aromaticity to attain highly symmetric structures with high electronic stability.…”
mentioning
confidence: 99%